Interview with the EULAR President - Vinall, Maria (MD Conference Express, 2012)
During the 2012 EULAR meeting, ‘MD Conference Express’ met with Maxime Dougados, MD, EULAR 2012 President, to discuss how the new research findings presented at EULAR and how those findings can be translated into daily practice.